A strategic culture analysis of German ballistic missile defense policy. Issue 4 (8th August 2017) - Kubiak, Katarzyna
ABSTRACT: Since the end of the Cold War, territorial ballistic missile defense (BMD) has played a key role in shaping relations between the U.S., NATO, and Russia. This article applies the concept of strategic culture to examine how Berlin rationalized and legitimized BMD and Germany's participation in the NATO BMD project. For Berlin, BMD served as a tool to strengthen NATO and held promise to paving the way to strategic partnership with Russia. With the current stalemate between NATO and Russia and the internal dissent within NATO over BMD's composition and role in its broader deterrence and defense posture, the German long-term strategic interest in BMD has lost relevance. Yet Berlin still has not established a new policy line on BMD. The article argues that the German cooperative strategic culture did not provide off-the-shelf alternatives that fit the changed geopolitical circumstances. It also did not adapt, but rather exhibited a prevalence for continuity.